2009
DOI: 10.1111/j.1440-169x.2009.01135.x
|View full text |Cite
|
Sign up to set email alerts
|

Infrared laser‐mediated local gene induction in medaka, zebrafish and Arabidopsis thaliana

Abstract: Heat shock promoters are powerful tools for the precise control of exogenous gene induction in living organisms. In addition to the temporal control of gene expression, the analysis of gene function can also require spatial restriction. Recently, we reported a new method for in vivo, single-cell gene induction using an infrared laser-evoked gene operator (IR-LEGO) system in living nematodes (Caenorhabditis elegans). It was demonstrated that infrared (IR) irradiation could induce gene expression in single cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
67
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 25 publications
(42 reference statements)
0
67
1
Order By: Relevance
“…In addition to increased expression, finely tuned spatial control imparted by laser stimulus could help solve persistent problems of gene expression in nontarget cells, which often occurs in existing techniques such as mosaic analysis. 20 To date, only a limited number of studies have reported the use of IR or near-IR (NIR) laser treatment with mesoporous silica; however, they require the use of gold cores and the associated plasmonic resonance in response to the laser photons. For example, Volodkin et al 47 demonstrated that gold cores inside MSNP pores could be heated with NIR light to transfer heat to liposome bilayer cargo to release encapsulated dye molecules, while Mura et al 48 reported that an increase in temperature of NIR-treated gold nanoparticle cores caused a phase transition in polymers capping mesoporous silica shells, allowing leakage of a preloaded drug.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to increased expression, finely tuned spatial control imparted by laser stimulus could help solve persistent problems of gene expression in nontarget cells, which often occurs in existing techniques such as mosaic analysis. 20 To date, only a limited number of studies have reported the use of IR or near-IR (NIR) laser treatment with mesoporous silica; however, they require the use of gold cores and the associated plasmonic resonance in response to the laser photons. For example, Volodkin et al 47 demonstrated that gold cores inside MSNP pores could be heated with NIR light to transfer heat to liposome bilayer cargo to release encapsulated dye molecules, while Mura et al 48 reported that an increase in temperature of NIR-treated gold nanoparticle cores caused a phase transition in polymers capping mesoporous silica shells, allowing leakage of a preloaded drug.…”
Section: Discussionmentioning
confidence: 99%
“…20,[39][40][41] To the best of our knowledge, there are presently no reports describing the use of molecular cargo driven by an HSP response to improve cargo expression by MSNP delivery in a thermodynamic manner. The use of DNA cargo itself as the responsive element is highly beneficial due to its naturally high cellular uptake and biocompatibility compared to the other responsive elements commonly associated with nanoparticles, such as gold spheres or chemical valves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 In this study, we attempted to control gene expression in the single endothelial cells in zebrafish. We identified each single endothelial cell by using zebrafish transgenic for fli1:nEGFP, and we used the IR laser to irradiate them individually, and induced the expression of mCherry by using the IR-LEGO ( Figure 1A-1C).…”
Section: Ir Laser-mediated Gene Expression In Targeted Single Endothementioning
confidence: 99%
“…We confirmed that this system was efficient in regulating spatiotemporal gene expression, and reported IR laser-mediated gene induction in single targeted cells in nematodes (Caenorhabditis elegans), 9 and the local gene expression in various tissues, such as the muscle, notochord, and retina in some living vertebrates, for example, zebrafish (Danio rerio) and medaka (Oryzias latipes). 10 In this study, we applied this IR-LEGO system to the vascular system in zebrafish and established, to the best of our knowledge, for the first time, an excellent method to induce laser-mediated gene expression in single targeted endothelial cells in vivo. We optimized the irradiation conditions, which resulted in raising the efficiency of laser-mediated gene induction up to 60%.…”
mentioning
confidence: 99%